A gas barrier nylon composite material and its preparation method and application
By using composite materials of PA6, impact modifiers, polyhydroxy compounds and cyclodextrins in the lining materials of high-pressure hydrogen storage tanks, the collapse and fracture problems during the molding process are solved, and gas barrier properties and heat resistance are improved Aging performance achieves better hydrogen barrier effect.
Patent Information
- Application Number
- CN202310461788.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-04-26
AI Technical Summary
The existing high-pressure hydrogen storage tank lining materials are prone to collapse or rupture during the molding process, and the addition of impact modifiers will reduce gas barrier properties and accelerate aging, resulting in a decrease in the heat resistance and barrier properties of the material.
A gas-barrier nylon composite material is used, containing PA6, impact modifier, polyhydroxy compound and cyclodextrin or its derivatives, and is prepared through a twin screw extrusion mechanism to form a crosslinked structure to improve elasticity and barrier properties. And enhance the intermolecular binding force of the material through hydrogen bonding.
It is achieved to prevent melt rupture during blow molding, improve wall thickness uniformity and heat aging resistance, and improve hydrogen barrier properties, avoid the decrease in gas barrier properties caused by impact modifiers.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a gas barrier nylon composite material and a preparation method and application thereof. Background Art
[0002] In recent years, the world has been continuously researching and rapidly developing fuel cell vehicles to cope with the energy crisis and climate problems caused by greenhouse gases. Fuel cells are installed on vehicles to generate electricity through electrochemical reactions between hydrogen and oxygen in the air, which continuously power the engine. Although the energy produced per unit mass of hydrogen is much higher than that of gasoline, and the reaction product is water, hydrogen is a gas at room temperature with low energy density. It needs to be pressurized to increase the energy density and improve the endurance of fuel vehicles. Therefore, high-pressure hydrogen storage tanks determine whether fuel cell vehicles are practical.
[0003] The number of storage tanks and the pressure of fuel cell vehicles determine the amount of gas carried. In order to achieve high-pressure gas storage and reduce the weight of the storage tank, the high-pressure hydrogen storage tank technology is constantly being innovated. Since hydrogen has a smaller molecular size than air, methane, etc., it is easier to penetrate the resin, and the strain caused by high-pressure hydrogen on the lining material is greater. Repeated filling and degassing can easily cause material fatigue and cracking. Polycaprolactam (PA6) has a high degree of crystallinity and can effectively inhibit hydrogen penetration.
[0004] In the prior art, the lining materials of high-pressure hydrogen storage tanks have the following difficulties:
[0005] First, the molding methods for preparing high-pressure hydrogen storage tank lining materials using polymer compositions include injection molding, rotational molding, extrusion blow molding, etc. Blow molding is usually used to mold large-sized parts with hollow structures. During blow molding, melt collapse or melt rupture will lead to molding failure. Therefore, the wall thickness of the hydrogen storage tank lining is required to be uniform and free of cracks.
[0006] Second, the existing hydrogen storage tank lining uses impact modifiers to improve toughness. On the one hand, the heat of the system during the filling and discharging process or the driving process of the fuel vehicle causes aging, especially the elastomer of the impact modifier usually ages before the polyamide substrate, resulting in a decrease in toughness. This factor accelerates the cracking of weak locations during repeated filling and discharging. Therefore, improving the heat aging resistance of the lining material of the high-pressure hydrogen storage tank is one of the key parameters. On the other hand, the addition of impact modifiers will destroy the gas barrier structure, thereby reducing the gas barrier properties of PA6. Therefore, how to improve the decrease in gas barrier properties caused by the addition of impact modifiers is one of the key concerns of the industry. Summary of the invention
[0007] The purpose of the present invention is to overcome the above technical defects and provide a gas barrier nylon composite material suitable for the lining of a high-pressure gas storage tank, which has the advantages of being suitable for blow molding, having good heat aging resistance and good hydrogen barrier properties.
[0008] The present invention is achieved through the following technical solutions:
[0009] A gas barrier nylon composite material, comprising the following components in parts by weight:
[0010] PA6 60 parts;
[0011] Impact modifier 0-30 parts;
[0012] 2.5-20 parts of polyhydroxy compounds;
[0013] 2.5-6 parts of cyclodextrin or its derivatives.
[0014] Preferably, the polyol content is 12-17 parts;
[0015] Preferably, the weight ratio of the polyhydroxy compound to cyclodextrin or its derivative is (3-4): 1. Under the preferred ratio, the gas barrier property is better.
[0016] Optionally, the relative viscosity of the PA6 is 2.7-4.5. The relative viscosity is measured according to ISO 307 by dissolving PA6 in 98% concentrated sulfuric acid using an Ubbelohde viscometer.
[0017] Optionally, the cyclodextrin or its derivative is selected from at least one of β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, sulfobutyl ether-β-cyclodextrin, disaccharide-β-cyclodextrin, methyl-β-cyclodextrin or hydroxyethyl-β-cyclodextrin.
[0018] The polyhydroxy compound is selected from at least one of a polyhydroxy compound containing two hydroxyl functional groups, a polyhydroxy compound containing three hydroxyl functional groups, a polyhydroxy compound containing at least four hydroxyl functional groups, and a polyhydroxy polymer containing at least four hydroxyl functional groups;
[0019] Preferably, the polyol compound is selected from polyol polymers containing at least four hydroxyl functional groups.
[0020] Optionally, the polyhydroxy compound containing two hydroxyl functional groups is selected from at least one of 1,2-ethylene glycol, 1,3-propylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 2,2-dimethyl-1,3-propylene glycol, and polyether glycols;
[0021] The polyol containing three hydroxyl functional groups is selected from glycerol, trimethylolpropane, 2,3-di(2′-hydroxyethyl)cyclohexane-1-ol, 1,2,6-hexanetriol, 1,1,1-tris-(hydroxymethyl)ethane, 3-(2′-hydroxyethoxy)propane-1,2-diol, 3-(2′-hydroxypropoxy)propane-1,2-diol, 2-(2′-hydroxyethoxy)hexane-1,2-diol, 6-(2′-hydroxypropoxy)hexane-1,2-diol, 1,1,1-tris[(2′-hydroxyethoxy) at least one of 1,1,1-tris[(2′-hydroxypropoxy)methyl]propane, 1,1,1-tris(4′-hydroxyphenyl)ethane, 1,1,1-tris(hydroxyphenyl)propane, 1,1,3-tris(dihydroxy-3-methylphenyl)propane, 1,1,4-tris(dihydroxyphenyl)butane, 1,1,5-tris(hydroxyphenyl)-3-methylpentane, di(trimethylolpropane), trimethylolpropane ethoxylates, trimethylolpropane propoxylates, and trihydroxy polyether compounds;
[0022] The polyhydroxy compound containing at least four hydroxyl functional groups is selected from at least one of 1,1,3,3-tetra(methoxy)propane, pentaerythritol, dipentaerythritol and tripentaerythritol;
[0023] The polyhydroxy polymer containing at least four hydroxyl functional groups is at least one selected from polyvinyl alcohol, ethylene vinyl alcohol copolymer, and dendritic hyperbranched polyester.
[0024] Optionally, the impact modifier is selected from at least one of maleic anhydride grafted ethylene-octene copolymer, polyethylene, polypropylene, polybutene, polyisoprene, ethylene-propylene rubber, ethylene-propylene-butadiene rubber, maleic anhydride grafted linear low density polyethylene, ethylene-butene rubber, ethylene-acrylate rubber, butadiene-styrene rubber, butadiene-acrylate rubber, ethylene-octene rubber, butadiene acrylonitrile rubber, ethylene-acrylic acid polymer, ethylene-vinyl acetate polymer, ethylene-acrylate polymer, maleic anhydride grafted ethylene butene copolymer, acrylonitrile-butadiene-styrene copolymer, styrene-ethylene-butadiene-styrene block copolymer, ethylene-butyl acrylate-glycidyl methacrylate, styrene-butadiene-styrene copolymer, and methacrylate-butadiene-styrene type core / shell elastomer.
[0025] It is also possible to decide whether to add 0-5 parts of an auxiliary agent according to actual needs, wherein the auxiliary agent is selected from at least one of an antioxidant, a lubricant, and a weathering agent.
[0026] The antioxidant may be a hindered phenol antioxidant (such as Irganox 1098) or a phosphite antioxidant (such as PEP-36).
[0027] The lubricant may be an ester lubricant or the like.
[0028] The weathering agent may be an anti-ultraviolet agent or the like.
[0029] The preparation method of the gas barrier nylon composite material of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, wherein the screw temperature ranges from 210 to 250° C. and the rotation speed ranges from 200 to 500 rpm to obtain the gas barrier nylon composite material.
[0030] The gas barrier nylon composite material of the present invention is used for the lining of a high-pressure gas storage tank.
[0031] The present invention has the following beneficial effects
[0032] The polyhydroxy structure on the outer edge of the cyclodextrin molecular structure is combined with PA6 through hydrogen bonding. The multi-functional groups provided by the polyhydroxy compounds provide intermolecular hydrogen bonding force with the PA6 polymer chain. The formed quasi-cross-linked structure is beneficial to improve the elastic storage modulus of the melt, especially under low-frequency shear or stretching, corresponding to the ability of the extrusion and blow molding process to resist tensile deformation of the melt, and it is not easy to cause melt fracture in blow molding of the product, so as to obtain a product with uniform wall thickness.
[0033] Cyclodextrin has a special ring structure, which forms a hydrophilic outer edge and a hydrophobic inner cavity, so that it can capture hydrogen molecules that attempt to penetrate the material from the inside through the Van der Waals effect of the hydrophobic cavity; at the same time, the dense structure formed by the polyhydroxy compound is also conducive to hindering the passage of gas molecules, which are dispersed around the impact modifier, so it can improve the decline in hydrogen barrier properties caused by the addition of impact modifiers. For low molecular weight barrier properties such as hydrogen molecules, it also means that it has the same effect on oxygen with a larger molecular volume, so to a certain extent, it prevents the internal impact modifier from being affected by high temperature aging and causing a decline in toughness. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0035] The raw materials used in the examples and comparative examples of the present invention are as follows:
[0036] PA6: Ultramid B40L, relative viscosity 3.8, BASF;
[0037] Impact modifier A: maleic anhydride grafted ethylene-octene copolymer (mPOE), purchased from DuPont, brand Fusabond N493;
[0038] Impact modifier B: maleic anhydride grafted linear low-density polyethylene (mLLDPE), purchased from UBE, brand name UBEBOND F3000;
[0039] Impact modifier C: maleic anhydride grafted ethylene butene copolymer (mEBA), purchased from Mitsui Chemicals, TAFMERMH5020;
[0040] Impact modifier D: ethylene-n-butyl acrylate-glycidyl methacrylate (E-nBA-GMA), purchased from DuPont, brand name Elvaloy PTW.
[0041] 1,5-Pentanediol: Sigma-Aldrich;
[0042] Glycerol: Sigma-Aldrich;
[0043] Pentaerythritol: Charmor PM40, purchased from Perstorp.
[0044] Polyvinyl alcohol A: purchased from Kuraray;
[0045] Polyvinyl alcohol B: purchased from Shanghai Yingjia.
[0046] Ethylene vinyl alcohol copolymer: purchased from Changchun Group.
[0047] β-Cyclodextrin: Sigma-Aldrich;
[0048] γ-Cyclodextrin: Sigma-Aldrich.
[0049] Embodiment and comparative example Preparation method of gas barrier nylon composite material: according to the ratio, the components are mixed evenly, and extruded into granules by a twin-screw extruder, the screw temperature range is 210-250°C, and the rotation speed range is 300-400rpm to obtain a PA6 composite material.
[0050] Various test methods:
[0051] (1) Gas barrier property: The granulated sample is injection molded into a 100×100×1mm sample, adapted to the gas permeability test cavity to form a disc, and the sample is installed between two cavities to form a sealed system. The gas exchange between the two cavities is only allowed to pass through the sample, one of which is the generating end of the target high-pressure gas (hydrogen) and the other is the collecting end for the target gas penetration. The amount of gas passing through the sample per unit area per unit time is recorded as the gas permeability, in cm 3 / (m 2*day). In this system, gas permeability is a characteristic of the sample itself. The permeability of the material needs to take into account the thickness of the sample itself and the partial pressure of the target gas, that is, permeability coefficient = gas permeability × sample thickness / target gas partial pressure, the unit is cm 3 cm / (cm 2 ·s·cmHg). The specific test conditions are relative humidity of 0%, test temperature of 23°C, helium partial pressure of 0.5MPa, and sample thickness of 1mm. The gas barrier properties are classified as follows:
[0052] Permeability ≤2.5×10 -11 , level 1;
[0053] 2.5×10 -11 <Permeability<5.0×10 -11 , level 2;
[0054] 5.0×10 -11 <Permeability≤2.5×10 -10 , level 3;
[0055] 2.5×10 -10 <Permeability, level 4;
[0056] (Permeability unit: cm 3 cm / (cm 2 ·s·cmHg))。
[0057] (2) Heat aging resistance: The unnotched impact strength test was conducted according to ISO179 to measure the initial unnotched impact strength. The aging temperature was 150°C, the aging cycle was 1000 hours, and the unnotched impact strength after aging was measured. The retention rate = unnotched impact strength after aging / initial unnotched impact strength*100%.
[0058] (3) Wall thickness uniformity: The evaluation was conducted using the HAAKE PolyLab OS multifunctional torque rheometer, with a circular extrusion die; the extrusion temperature was 250-280°C, the rotation speed was 250 rpm, and after extruding a sample of about 8-10 cm, the bottom of the extruded sample was clamped with tweezers. The high-pressure gas valve connected to the core layer pipeline of the circular die was opened, nitrogen was filled in, and the gas valve pressure was adjusted to control the gas flow rate at 0.15 m / s. 3 / min, close the air valve after inflating for 5s. Wait for the blown extrudate to cool to room temperature, and remove the blow-molded sample from the extrusion die. In order to measure the wall thickness, cut the blow-molded sample from the middle perpendicular to the extrusion direction. Measure each point on the circumference of the section in 8 equal parts, calculate the relative deviation, unit %, and make the following ratings based on the relative deviation:
[0059] Relative deviation ≤5%, level 1;
[0060] 5%<Relative deviation≤10%, Level 2;
[0061] 10%<Relative deviation≤20%, Level 3;
[0062] 20%<Relative deviation≤30%, Level 4;
[0063] Relative deviation>30%, level 5.
[0064] Table 1: Content of each component (parts by weight) and test results of gas barrier nylon composite materials of Examples 1-7
[0065] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA6 60 60 60 60 60 60 60 Impact Modifier A 0 5 15 30 Impact Modifier B 15 Impact Modifier C 15 Impact modifier D 15 1,5-Pentanediol 10 10 10 10 10 10 10 β-Cyclodextrin 3 3 3 3 3 3 3 Gas barrier properties 1 1 1 2 2 2 2 Unnotched impact strength retention rate, % 53 51 48 47 46 47 47 Wall thickness uniformity 2 2 2 2 2 2 2
[0066] In Example 1-4, the gas barrier property and the wall thickness uniformity as well as the heat aging resistance can be significantly improved by compounding 1,5-pentanediol / β-cyclodextrin.
[0067] Table 2: Content of each component (parts by weight) and test results of gas barrier nylon composite materials of Examples 8-15
[0068] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 PA6 60 60 60 60 60 60 60 60 Impact Modifier A 10 10 10 10 10 10 10 10 1,5-Pentanediol 2.5 10 12 17 20 12 12 12 β-Cyclodextrin 4 4 4 4 4 3 6 2.5 Gas barrier properties 2 2 1 1 2 1 2 2 Unnotched impact strength retention rate, % 49 50 51 54 48 55 46 48 Wall thickness uniformity 2 2 1 1 2 1 2 2
[0069] It can be seen from Examples 8-12 that the preferred content of the polyhydroxy compound is 12-17 parts.
[0070] It can be seen from Examples 10 / 13-15 that the preferred weight ratio of the polyhydroxy compound to cyclodextrin or its derivative is (3-4):1.
[0071] Table 3: Content of each component (parts by weight) and test results of gas barrier nylon composite materials of Examples 16-20
[0072] Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Embodiment 21 PA6 60 60 60 60 60 60 Impact Modifier A 10 10 10 10 10 10 1,5-Pentanediol 12 glycerin 10 Pentaerythritol 10 Polyvinyl alcohol A 10 Polyvinyl alcohol B 10 Ethylene Vinyl Alcohol Copolymer 10 β-Cyclodextrin 4 4 4 4 4 γ-Cyclodextrin 4 Gas barrier properties 2 1 1 1 1 1 Unnotched impact strength retention rate, % 50 53 55 54 56 53 Wall thickness uniformity 1 1 1 1 1 1
[0073] It can be seen from Examples 9 / 16-19 that polyhydroxy polymers containing at least four hydroxyl functional groups are preferred, as they have higher gas barrier properties and thus better resistance to thermal aging and oxidation.
[0074] Table 4: Comparative Example Gas Barrier Nylon Composite Material Component Content (Parts by Weight) and Test Results
[0075] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PA6 60 60 60 60 60 60 60 Impact Modifier A 10 10 10 10 10 0 20 1,5-Pentanediol 12 12 12 0 25 0 0 β-Cyclodextrin 0 1 8 4 4 0 0 Gas barrier properties 3 3 2 4 2 3 4 Unnotched impact strength retention rate, % 29 33 38 14 41 25 13 Wall thickness uniformity 4 3 4 2 4 2 4
[0076] It can be seen from Comparative Examples 1-5 that the content of polyhydroxy compound / cyclodextrin is not within the scope of the present invention, and it is impossible to ensure that the hydrogen barrier property, heat oxygen aging resistance, and uniformity of the wall thickness of the blow-molded parts meet the requirements.
[0077] It can be seen from Comparative Examples 6 / 7 that an increase in the impact modifier content will destroy the gas barrier structure of the nylon composite material and the uniformity of the wall thickness, and will also lead to a decrease in the retention rate of the unnotched impact strength.
Claims
1. A gas barrier nylon composite material, characterized in that: By weight, it includes the following components: PA6 60 parts; Impact modifier 0-30 parts; 12-17 parts of polyol; 2.5-6 parts of cyclodextrin or its derivatives; The weight ratio of the polyhydroxy compound to the cyclodextrin or its derivative is (3-4):1; The cyclodextrin or its derivative is selected from at least one of β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, sulfobutyl ether-β-cyclodextrin, disaccharide-β-cyclodextrin, methyl-β-cyclodextrin or hydroxyethyl-β-cyclodextrin; The polyhydroxy compound is selected from at least one of a polyhydroxy compound containing two hydroxyl functional groups, a polyhydroxy compound containing three hydroxyl functional groups, a polyhydroxy compound containing at least four hydroxyl functional groups, and a polyhydroxy polymer containing at least four hydroxyl functional groups; The polyhydroxy compound containing two hydroxyl functional groups is selected from at least one of 1,2-ethylene glycol, 1,3-propylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 2,2-dimethyl-1,3-propylene glycol, and polyether glycols; The polyhydroxy compound containing three hydroxyl functional groups is selected from at least one of glycerol, trimethylolpropane, 2,3-bis(2′-hydroxyethyl)cyclohexane-1-ol, 1,2,6-hexanetriol, 1,1,1-tris-(hydroxymethyl)ethane, 3-(2′-hydroxyethoxy)propane-1,2-diol, 3-(2′-hydroxypropoxy)propane-1,2-diol, 2-(2′-hydroxyethoxy)hexane-1,2-diol, 6-(2′-hydroxypropoxy)hexane-1,2-diol, 1,1,1-tris[(2′-hydroxyethoxy)methyl]ethane, 1,1,1-tris[(2′-hydroxypropoxy)methyl]propane, 1,1,1-tris(4′-hydroxyphenyl)ethane, 1,1,1-tris(hydroxyphenyl)propane, 1,1,5-tris(hydroxyphenyl)-3-methylpentane, and trihydroxy polyether compounds; The polyhydroxy compound containing at least four hydroxyl functional groups is selected from at least one of di(trimethylolpropane), 1,1,3-tri(dihydroxy-3-methylphenyl)propane, 1,1,4-tri(dihydroxyphenyl)butane, pentaerythritol, dipentaerythritol, and tripentaerythritol. The polyhydroxy polymer containing at least four hydroxyl functional groups is selected from at least one of polyvinyl alcohol, ethylene vinyl alcohol copolymer, and dendritic hyperbranched polyester.
2. The gas barrier nylon composite material according to claim 1, characterized in that: The relative viscosity of the PA6 is 2.7-4.
5. According to ISO 307, PA6 is dissolved in 98% concentrated sulfuric acid and measured using an Ubbelohde viscometer.
3. The gas barrier nylon composite material according to claim 1, characterized in that: The polyol compound is selected from polyol polymers containing at least four hydroxyl functional groups.
4. The gas barrier nylon composite material according to claim 1, characterized in that: The impact modifier is selected from at least one of maleic anhydride grafted ethylene-octene copolymer, polyethylene, polypropylene, polybutene, polyisoprene, ethylene-propylene rubber, ethylene-propylene-butadiene rubber, maleic anhydride grafted linear low-density polyethylene, ethylene-butene rubber, butadiene-styrene rubber, butadiene-acrylate rubber, ethylene-octene rubber, butadiene acrylonitrile rubber, ethylene-acrylic acid polymer, ethylene-vinyl acetate polymer, ethylene-acrylate polymer, maleic anhydride grafted ethylene butene copolymer, acrylonitrile-butadiene-styrene copolymer, styrene-ethylene-butadiene-styrene block copolymer, ethylene-butyl acrylate-glycidyl methacrylate, styrene-butadiene-styrene copolymer, and methacrylate-butadiene-styrene type core / shell elastomer.
5. The gas barrier nylon composite material according to claim 1, characterized in that: The impact modifier is selected from ethylene-acrylate rubber.
6. The gas barrier nylon composite material according to claim 1, characterized in that: The invention also includes 0-5 parts of auxiliary agents by weight, wherein the auxiliary agents are selected from at least one of antioxidants, lubricants and weathering agents.
7. The method for preparing the gas barrier nylon composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating the components through a twin-screw extruder, wherein the screw temperature range is 210-250° C. and the rotation speed range is 200-500 rpm, so as to obtain a gas barrier nylon composite material.
8. Use of the gas barrier nylon composite material according to any one of claims 1 to 6, characterized in that: Used for lining of high pressure gas storage tanks.